Gestational exposure to arsenic reduces female offspring fertility by impairing the repair of DNA double-strand breaks and synapsis formation in oocytes - Cong Ma; Kaiqin Hu; Xueke Zhang; Yaru Yu; Zuying Xu; Tian Ma; Hongzhen Ruan; Yingying Zhang; Jiajia Wang; Xinyu Yue; Chunmei Liang; Huifen Xiang; et al. (Ecotoxicology and Environmental Safety)
Arsenic is a pollutant that can cross the placenta; however, research on the effects of arsenic exposure during pregnancy on the fertility of female offspring is limited. To address this gap, we developed a mouse model to investigate the relationship between arsenic exposure during pregnancy and fertility in female offspring. Our fertility assessment revealed that gestational exposure to 1 mg/kg arsenic or higher (10 mg/kg) resulted in reduction in litter size, ovarian volume, and multistage-follicle number in female offspring. By assessing the in vitro developmental capacity of oocytes and zygotes, we confirmed that the reduced fertility was due not to impaired oocyte quality but rather to a reduction in oocyte quantity. Arsenic exposure impedes synapsis formation in MPI and compromises homologous recombination-mediated repair of double-strand breaks, resulting in fewer crossovers. This disruption activates the pachytene-checkpoint, hindering the progression of the MPI and resulting in the elimination of defective oocytes through p-Chk2 activation. Our study reveals for the first time the detrimental effects of arsenic exposure during pregnancy on the fertility of female offspring, underscoring the urgent need to prevent such exposure to safeguard reproductive health.